Non-coding RNAs in necroptosis, pyroptosis, and ferroptosis in cardiovascular diseases - Cai, Yuxi; Zhou, Yiwen; Li, Zhangwang; Xia, Panpan; ChenFu, Xinxi; Shi, Ao; Zhang, Jing; Yu, Peng (Frontiers in Cardiovascular Medicine, 2022)
Accumulating evidence has proved that non-coding RNAs (ncRNAs) play a critical role in cardiovascular diseases' genetic programming and gene regulation (CVDs). Cardiovascular disease morbidity and mortality are on the rise and has become a primary public hygiene issue that requires immediate resolution through effective intervention. Numerous studies have revealed that new types of cell death, such as pyroptosis, necroptosis, and ferroptosis, play critical cellular roles in CVD progression. It is worth noting that ncRNAs are critical novel regulators of cardiovascular risk factors and cell functions by mediating pyroptosis, necroptosis, and ferroptosis. Thus, ncRNAs can be regarded as promising therapeutic targets for treating and diagnosing cardiovascular diseases. Recently, there has been a surge of interest in the mediation of non-coding RNAs (ncRNAs) on three types of cell death in regulating tissue homeostasis and pathophysiological conditions in CVDs. Although our understanding of ncRNAs remains in its infancy, the studies reviewed here may provide important new insights into how ncRNAs interact with CVDs. This review summarizes what is known about the functions of ncRNAs in modulating cell death-associated CVDs and their role in CVDs, as well as their current limitations and future prospects.